Neuropsychopharmacological Understanding for Therapeutic Application of Morphinans - Shin, Eun-Joo (2010)
Morphinans are a class of compounds containing the basic structure of morphine. It is well-known that morphinans possess diverse pharmacological effects on the central nervous system. This review will demonstrate novel neuroprotective effects of several morphinans such as, dextromethorphan, its analogs and naloxone on the models of multiple neurodegenerative disease by modulating glial activation associated with the production of a host of proinflammatory and neurotoxic factors, although dextromethorphan possesses neuropsycotoxic potentials. The neuroprotective effects and the therapeutic potential for the treatment of excitotoxic and inflammatory neurodegenerative diseases, and underlying mechanism of morphinans are discussed.